1987
DOI: 10.1002/jat.2550070207
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of dimethylarsinic acid in mouse, hamster and man

Abstract: The metabolism of dimethylarsinic acid (DMA) a common pesticide and the main metabolite of inorganic arsenic in mammals, has been studied in mice, hamsters and man. Mice and hamsters were administered a single dose of 74As-DMA (40 mg As/kg body weight) orally, while a human subject ingested DMA corresponding to 0.1 mg As/kg body weight. Ion exchange chromatography, paper electrophoresis, thin layer chromatography as well as arsine generation--gas chromatography combined with atomic absorption spectrophotometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 36 publications
4
101
0
2
Order By: Relevance
“…Yamauchi and Yamamura (1984) reported that 49% of a single oral dose of 50 mg/kg DMA was eliminated in the urine of Syrian golden hamsters within 5 days ( 36% in feces). Marafante et al (1987) reported similar findings in that 56% of a single oral dose of 40 mg (As)/kg DMA was eliminated in urine of male Syrian golden hamsters within 48 h (41% in feces). Gastrointestinal absorption of DMA may be more extensive in mice.…”
Section: Metabolism and Dispositionsupporting
confidence: 59%
See 1 more Smart Citation
“…Yamauchi and Yamamura (1984) reported that 49% of a single oral dose of 50 mg/kg DMA was eliminated in the urine of Syrian golden hamsters within 5 days ( 36% in feces). Marafante et al (1987) reported similar findings in that 56% of a single oral dose of 40 mg (As)/kg DMA was eliminated in urine of male Syrian golden hamsters within 48 h (41% in feces). Gastrointestinal absorption of DMA may be more extensive in mice.…”
Section: Metabolism and Dispositionsupporting
confidence: 59%
“…DMA is methylated to trimethylarsenic compounds to a small extent in mice, rats, hamsters and humans (Yamauchi and Yamamura, 1984;Marafante et al, 1987;Yoshida et al, 1997). Marafante et al (1987) reported that 3 and 6% of a single oral dose of 40 mg (As)/kg DMA was eliminated in urine as trimethylarsine oxide (TMAO) within 48 h in mice and hamsters, respectively; TMAO was not detected in the feces of either species in this study.…”
Section: Metabolism and Dispositionmentioning
confidence: 65%
“…Upon exposure to arsenic, humans excrete significant amount of MMA which is about 10-20% of total urine arsenic 16 . In mammals DMA is the end point of arsenic metabolism and is not further methylated 17,18 . It is found that 40-60% of arsenic remains are retained in skin, hair, nails, muscle, teeth and bones even after exposure to arsenic is ceased (ATSDR case studies in environmental medicine, agency for toxic substances and disease registry) 19 .…”
Section: Metabolism Of Arsenicmentioning
confidence: 99%
“…The excreted dimethylated arsenic is roughly 50% and monomethylated is nearly 25% and the remaining is inorganic (Buchet et al 1981). MMA V and DMA V, the pentavalent metabolites have low toxicity as compared to arsenite or arsenate (Marafante et al 1987). An issue of National Health and Nutrition Examination Survey 2003-2004 on urinary arsenic suggests that as the total arsenic in the urine increases, there is increase in the percentage of methylated forms and as the total arsenic levels decreases in urine, inorganic arsenic is the leading element (Caldwell et al 2009).…”
Section: Excretionmentioning
confidence: 99%